2022
DOI: 10.1111/jvim.16437
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the etiology, risk factors, and pathogenesis of pancreatitis in dogs: Potential impacts on clinical practice

Abstract: While most cases of pancreatitis in dogs are thought to be idiopathic, potential risk factors are identified. In this article we provide a state‐of‐the‐art overview of suspected risk factors for pancreatitis in dogs, allowing for improved awareness and detection of potential dog‐specific risk factors, which might guide the development of disease prevention strategies. Additionally, we review important advances in our understanding of the pathophysiology of pancreatitis and potential areas for therapeutic manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 191 publications
(465 reference statements)
0
25
1
Order By: Relevance
“…Indeed, corticosteroids are now being used with increasing frequency in the management of acute pancreatitis [ 40 , 41 ]. In contrast with those results, our study showed a moderate frequency of corticosteroid use prior to sampling in dogs with increased Spec cPL concentrations, and this may reflect the presence of concurrent disease treated with corticosteroids or secondary pancreatic inflammation influenced by concurrent disease [ 8 ]. We cannot, however, rule out the potential that corticosteroids caused pancreatitis in some of the dogs in our study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Indeed, corticosteroids are now being used with increasing frequency in the management of acute pancreatitis [ 40 , 41 ]. In contrast with those results, our study showed a moderate frequency of corticosteroid use prior to sampling in dogs with increased Spec cPL concentrations, and this may reflect the presence of concurrent disease treated with corticosteroids or secondary pancreatic inflammation influenced by concurrent disease [ 8 ]. We cannot, however, rule out the potential that corticosteroids caused pancreatitis in some of the dogs in our study.…”
Section: Discussioncontrasting
confidence: 91%
“…Many diseases have been identified as potential risk factors for pancreatitis in dogs, including endocrinopathies, hypertriglyceridemia, infectious agents, and other miscellaneous disorders [ 8 ]. Hyperadrenocorticism (HAC) was reported in the history of 12/101 dogs with pancreatitis in one retrospective study, and in another study, dogs with HAC had higher cPLI concentrations than a control group of dogs [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute pancreatitis is known to induce multi-organ dysfunction due to activation of proteolytic enzymes, 1 and neutrophils and macrophages also play a key role in inflammatory responses in acute pancreatitis. 2 Phospholipase A2 (PLA2), a lipolytic enzyme, is a key regulatory enzyme in the generation of prostanoids, 3 and a significant increase in type II PLA2 activity has been thought to contribute to the pathogenesis of acutepancreatitis. 4 Previously, fuzapladib sodium monohydrate (IKV-741,N-[2-(ethylsulfonylamino)-5-(trifluoromethyl)-3-pyridinyl]cyclohexanecarboxamide mono sodium salt monohydrate) was developed as a potent phospholipase A2 inhibitor.…”
Section: Introductionmentioning
confidence: 99%